2019
DOI: 10.1080/07399332.2019.1615914
|View full text |Cite
|
Sign up to set email alerts
|

Spousal support and knowledge related to cervical cancer screening: Are Sub-Saharan African immigrant men interested?

Abstract: There are significant disparities in rates of cervical cancer screening for Sub-Saharan African immigrant (SSAI) women in the United States (U.S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 34 publications
8
9
0
Order By: Relevance
“…This was evidenced by the degree of importance given to screening, the willingness to discuss, approve and sponsor cervical screening for their wives. This finding is in agreement with other similar studies conducted to assess the attitude of men towards involvement in cervical cancer screening [ 10 , 11 , 17 , 20 ]. This favourable attitude of men towards involvement in reproductive health has been also documented in other studies on other reproductive health issues such as family planning and prevention of mother to child transmission of HIV [ 21 - 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…This was evidenced by the degree of importance given to screening, the willingness to discuss, approve and sponsor cervical screening for their wives. This finding is in agreement with other similar studies conducted to assess the attitude of men towards involvement in cervical cancer screening [ 10 , 11 , 17 , 20 ]. This favourable attitude of men towards involvement in reproductive health has been also documented in other studies on other reproductive health issues such as family planning and prevention of mother to child transmission of HIV [ 21 - 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, they were also willing to encourage their partners to go for screening. Similar findings have also been established in the literature among men in Kenya [16], and Uganda [17] as well as sub-Saharan African immigrant men [18]. In this study, most of the men believe that they will quickly seek medical attention for the disease and provide any necessary support that will be prescribed by the medical personnel, in order to help treat their female partners.…”
Section: Discussionsupporting
confidence: 85%
“…The findings show that men had little or no knowledge about the disease. A number of previous studies have also shown that men have low or inadequate cervical cancer knowledge [1618]. In this study, it has been observed that the men did not have any information about the causes and symptoms of the disease as well as the risk factors of the disease.…”
Section: Discussionmentioning
confidence: 66%
“… 63 When husbands receive health education about CCS and HPV, they can support their wives by providing emotional support, including empathy, love, trust, and caring, instrumental support including all direct care need by the person, and informational support, including the provision of advice, suggestions, and information to accomplish the goal. 76 The screening uptake among COMW in the control group was very poor because they had inadequate knowledge of cervical cancer and CCS. They were not informed about cervical cancer causes, risk factors, signs and symptoms, prevention of cervical cancer, and advantages of cervical cancer screening.…”
Section: Discussionmentioning
confidence: 99%